2017
DOI: 10.5194/wes-2-1-2017
|View full text |Cite
|
Sign up to set email alerts
|

On the impact of non-Gaussian wind statistics on wind turbines – an experimental approach

Abstract: Abstract. The effect of intermittent and Gaussian inflow conditions on wind energy converters is studied experimentally. Two different flow situations were created in a wind tunnel using an active grid. Both flows exhibit nearly equal mean velocity values and turbulence intensities but strongly differ in their two point statistics, namely their distribution of velocity increments on a variety of timescales, one being Gaussian distributed, and the other one being strongly intermittent. A horizontal axis model w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
27
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 28 publications
2
27
0
2
Order By: Relevance
“…The heavy-tailed distributions are the statistical descrip-5 tion of large velocity changes over given time scales and are transfered to turbines in terms of loads and power output. This has been shown experimentally (Schottler et al, 2017c), numerically (Mücke et al, 2011) and in a field study by Milan et al (2013). Consequently, our findings should be considered in wind farm layout optimization approaches, where a wake's width affects radial turbine spacing.…”
supporting
confidence: 66%
See 3 more Smart Citations
“…The heavy-tailed distributions are the statistical descrip-5 tion of large velocity changes over given time scales and are transfered to turbines in terms of loads and power output. This has been shown experimentally (Schottler et al, 2017c), numerically (Mücke et al, 2011) and in a field study by Milan et al (2013). Consequently, our findings should be considered in wind farm layout optimization approaches, where a wake's width affects radial turbine spacing.…”
supporting
confidence: 66%
“…We believed that distributions of velocity increments in wakes are of importance for potential downstream turbines as extreme events are likely to be transfered to wind turbines in terms of fluctuating loads and power output. Studies show this for a generic turbine model (Mücke et al, 2011), in a wind tunnel experiment (Schottler et al, 2017c) and by analyzing field data of a full-scale wind farm (Milan et al, 2013). Those findings make an investigation of velocity increments in wakes extremely 30 relevant for active wake control concepts as well as for wind farm layout approaches.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…To what extent statistical characteristics of velocity increments are transferred to wind turbines is of current interest throughout the research community (van Kuik et al, 2016). Schottler et al (2017c) found a transfer of intermittency from wind to torque, thrust and power data in a wind tunnel experiment using a model wind turbine. Similarly, Mücke et al (2011) found a transfer of intermittency to torque data using a generic turbine model.…”
Section: Introductionmentioning
confidence: 99%